Media System Dependency and Psychological Effects of Indonesian Migrant Worker Conflict News in South Sulawesi - Arham Selo; Asni Djamereng; Sadhriany Pertiwi Saleh; Muhammad Ilham; Mirwan (Yayasan Darussalam Bengkulu, 2026)
Online media has become a primary source for people in South Sulawesi to follow news about conflicts involving Indonesian Migrant Workers (PMI), an issue closely connected to families in migrant-sending areas. This study examines patterns of media system dependency and their cognitive, affective, and conative psychological effects on online news readers. Using a qualitative descriptive-phenomenological approach, data were collected through in-depth interviews with ten purposively selected informants from diverse backgrounds in Makassar City and PMI-sending areas. Data were analyzed using the Miles and Huberman interactive model, while validity was ensured through source triangulation and member checking. The findings identify three dependency patterns: emotional dependency among PMI families and returnees, verifiable dependency among media-literate groups, and incidental dependency among general readers. These patterns produce varying psychological effects, including strengthened knowledge accompanied by information ambiguity, persistent anxiety resembling doomscrolling, and changes in family communication and participation in social advocacy. The study extends Media System Dependency Theory by showing that dependency motivation, rather than consumption intensity alone, shapes the magnitude of psychological effects.